THE GENESIS AND POETIC INTERPRETATION OF THE WOLF IMAGE IN ENGLISH AND UZBEK FAIRY TALES: https://doi.org/10.5281/zenodo.17250165 - Teshaboyeva , Nafisa (International scientific and practical conference, 2025)
this article explores the genesis and poetic interpretation of the wolf image in English and Uzbek fairy tales. It examines how historical, cultural, and ecological contexts shaped the symbolic meanings of the wolf in both traditions. In English folklore, the wolf is predominantly portrayed as a villainous predator, embodying greed, deception, and moral danger, as seen in tales such as Little Red Riding Hood and The Three Little Pigs. In contrast, Uzbek folklore presents a more ambivalent image: the wolf appears both as a totemic ancestor and sacred guide in mythological epics like the O‘g‘uznoma, and as a cunning predator in household tales such as Bo‘ri va echki bolalari. The study highlights the poetic functions of the wolf image, including metaphor, repetition, exaggeration, and symbolic ambivalence. Through comparative analysis, the article demonstrates that while English tales emphasize moral caution and Christian allegory, Uzbek tales reflect nomadic traditions, humor, and mythological reverence. Ultimately, the wolf emerges as a powerful poetic archetype that bridges the realms of fear and reverence, chaos and order, across two distinct cultural traditions.